Monitoring of fouling and clean-in-place (CIP) using the Rotoscope and microscopy and monitoring of trihalomethanes (THMs) produced from electro chemically activated (ECA) water during CIP - Cloete, T.E. (Thomas Eugene), 1958- (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.